Spacing and Genotype on Height and Diameter Growth of Four Eucalyptus under Short Rotation - Balozi B Kirongo; Angela S Mbelase; Kingiri Senelwa; Joseph Hitimana; Lazare Etiegni (Jurnal Manajemen Hutan Tropika, 2012)
In this paper, the dynamic change in tree height, diameter at breast height (dbh), and ground line diameter (gld) at different density was studied. Trial sites were established in Chepkoilel and Nangili areas of western Kenya. Eight tree species (2 hybrid eucalyptus clones; GC 10 and GC 167), 1 eucalyptus local landrace, 2 agroforestry (Grevillea robusta and Markhamia lutea), 1 pure eucalyptus (Eucalyptus grandis), and 2 preferred local species (Maesopsis eminii and Khaya nyasica) were planted on each site. This paper however focuses on the effect of spacing on the height, dbh, and gld growth of the 4 eucalyptus genotypes viz (2 eucalyptus hybrid clones, 1 eucalyptus local landrace, and 1 pure Eucalyptus grandis). These were planted at 10 different spacings (0.6-, 0.8-, 1.0-, 1.2-, 1.4-, 1.6-, 1.8-, 2.0-, 2.2-, and 2.4-by-1.0 m; these being some of the most common spacings used by farmers) in a Nelder radial experimental design in 4 replications. Measurements of height, dbh, and gld were taken at intervals of 6 months over 3 years. The data was subjected to an analysis of variance to determine if there were statistically significant (p = 0.05) differences in tree growth with spacing levels. The results showed that tree growth was significantly influenced by spacing and genotype with the best spacing being 2.4-by-1.0 m, indicated that the relative growth rates of height dbh, gld, and increased with increasing the distance between trees but decreased with age. After 3 years the best spacing for optimal overall tree growth was 2.4-by-1.0 m and GC10 being the outstanding genotype. Of the 2 sites, trees performed better in Nangili. The results from this study further pinpoint the importance of species-site-matching using improved germplasm and planting trees at the correct spacing for optimal growth.